Alcohol and light-polymerizing glaze effect on the physical and mechanical properties of a bisacrylate composite resin before and after immersion in chlorhexidine gluconate - Commar, Betina Chiarelo [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; Silva, Clarissa Bruno [UNESP]; Bitencourt, Sandro Basso [UNESP]; Penitente, Paulo Augusto [UNESP]; Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP] (Elsevier, 2021)
Statement of problem: The use of 0.12% chlorhexidine gluconate (CHX) may damage bisacrylate composite resin interim restorations, but whether they can be protected with an application of alcohol and/or the use of a glaze is unclear. Purpose: The purpose of this in vitro study was to evaluate the effect of applying a 70% alcohol solution on the physical and mechanical properties of a bisacrylate composite resin, with and without the application of a light-polymerizing glaze subjected to 0.12% CHX twice a day for 7 days. Material and methods: Forty specimens of an autopolymerized bisacrylate composite resin were divided into 4 groups (n=10): Group C (without alcohol, without glaze), Group G (without alcohol, with glaze), Group A (with alcohol, without glaze), and Group AG (with alcohol, with glaze). All specimens were submitted to in vitro treatment with 0.12% CHX for 7 days, and tests of color alteration (ΔE00), microhardness, roughness, and surface were performed initially and after treatment. Data were submitted to analysis of variance (ANOVA) and the Tukey HSD test (α=.05). Results: Group A had the lowest mean value of ΔE00 with a significant statistical difference from Group C. The groups with alcohol presented higher microhardness mean values compared with groups without alcohol in both periods of analysis, except for the groups with glaze in the final period. Group C showed higher mean roughness values in comparison with Group A in both periods. Group AG presented higher mean roughness values than Group G. Surface energy values did not vary significantly among groups, except between Groups C and A in the final period. Conclusions: The application of alcohol optimized the properties of the autopolymerized bisacrylate composite resin analyzed, with and without the application of glaze. Overall, the use of CHX changed the microhardness and roughness when the glaze was applied.